Proceedings of 38th International Cosmic Ray Conference — PoS(ICRC2023) 2023
DOI: 10.22323/1.444.0775
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-ray emission from molecular clouds illuminated by local young massive stellar clusters and detection prospects with current and next generation instruments

Abstract: Cosmic ray acceleration up to PeV energies has been suggested to take place in massive and young stellar clusters. The formation of a strong termination shock sustained by the collective action of stellar winds in a compact cluster offers a promising location where efficient particle acceleration might take place. The subsequent hadronic interactions of these particles result into gammaray production: in particular, if dense clouds are located within and around clusters, enhanced emission is expected. Within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Since several years there has been an increase interest to investigate the origin of their VHE 𝛾-ray emission through spectral and morphological studies. There are several models manage to get particles up to PeV energies [60,61] and prospects to search for their signatures [62] not only in gamma rays, but also in neutrinos. For sources like the Cygnus Cocoon [63] it was shown that synchrotron emission limits the lepton contribution at the highest energies to be less than 25% emission beyond PeV in LHAASO data [64].…”
Section: Stellar Clustersmentioning
confidence: 99%
“…Since several years there has been an increase interest to investigate the origin of their VHE 𝛾-ray emission through spectral and morphological studies. There are several models manage to get particles up to PeV energies [60,61] and prospects to search for their signatures [62] not only in gamma rays, but also in neutrinos. For sources like the Cygnus Cocoon [63] it was shown that synchrotron emission limits the lepton contribution at the highest energies to be less than 25% emission beyond PeV in LHAASO data [64].…”
Section: Stellar Clustersmentioning
confidence: 99%